Sentenças Proverbiais: um estudo sintático-semântico de bases enunciativas - Priscila Brasil Goncalves Lacerda (2009)
This work presents a study of the sentences structured as He who x y or Those who x y, which we designate as proverbial sentences. We propose to explain the syntactic and semantic configuration of these sentences from the theoretical perspective of a syntax of enunciative bases (DIAS, 2002), which, in turn, is related to a semantics of enunciation. This theoretical basis gives us support to comprehend the syntactical fact in the interface between the organic (material) and symbolic (enunciative) dimensions of the language, thus, focusing on the positions of the grammatical subject and object, considering that these are positions ofreference configuration (DIAS, 2006a), so that we can recognize the enunciative specificities of each of these syntactic positions in the creation of a proverbial reference. We investigate precisely how the semantic-enunciative traces that we recognize as definers of the sentence group with which we worked, i. e., the traces of genericity, omnitemporality and indiciality and implicative sense, inscribe themselves in the organicity of these sentences. Through thisprocess, we seek to elucidate also the constitution itself of these traces. Finally, our work proposes to define the constitution of what we call mode of proverbial enunciation, producing an application of a syntax of enunciative bases.